Detection of Antibodies to Dengue Virus Infection among Eligible Blood Donors in Hadhramout Coast/Yemen - Tahani Aidaros Al-Afifi, (Enhanced Knowledge in Sciences and Technology, 2022)
Dengue fever is a tropical and subtropical disease, it is one of the most common viral diseases in the world transmitted by the Aeades mosquito. Threat to blood transfusion transmitted dengue virus (DENV) has recently emerged worldwide, and the risk of transfusion transmitted dengue has been increasingly recognized. Blood donors in an endemic area like Hadhramout coast may serve as a potential vehicle for transmission of the DENV infection. So, this cross-sectional study was aimed to determine the seroprevalence of asymptomatic DENV infection and its antibodies among eligible blood donors in Hadhramout coast regions/Yemen. Serum samples were collected from 229 blood donors residents from the main hospitals in Hadhramout coast region. Our results revealed that 23(10%) and 73(32%) were seropositive for anti-DENV IgM and IgG respectively among the tested blood donors. The age group 30-39 years was the most prevalent of DENV infection, followed by the age group 20-29 years, high rate prevalence of DENV infection also was found in the urban areas, as well as all the geographical regions studied showed prevalence of DENV infection. Statistically, study revealed no significant correlation showed between complete blood count (CBC) profile results with positive and negative results of DENV infection among blood donors. In brief, high prevalence of asymptomatic DENV infection and its antibodies among blood donors increasing the importance of establishing blood screening for dengue disease at different blood donation services in Hadhramout coast to improve the guarantee of blood transfusions and control DENV dissemination. anti-DENV IgM among the tested donors reflects their ongoing asymptomatic viremic infection stage with DENV during blood donation time, whereas high seroprevalence of anti-DENV IgG reflects the endemicity of dengue disease in Hadhramout coast regions.